Dividing Global Business Process: Safeguarding Confidential Data - Wulan Purnamasari; Didik Setiawan; Zainul Wasik; Suwandi S. Sangadji (PT. Mawadaku Sukses Solusindo, 2024)
This study shows that manufacturing unit process dispersion serves as an operational-level variable that allows businesses to modify their information protection strategy when it comes to sourcing business services overseas to suit the regulatory framework of the chosen host nation as well as the potential for using internal controls over activities carried out overseas. Our hypothesis is that businesses are more inclined to split up their processes among several foreign production facilities rather of concentrating every procedure duties in one unit when the aforementioned mechanisms are unavailable. Businesses may take advantage of the synergies between the scattered pieces of a process while lowering the risk of individual fragment theft because of IT-enabled integration capabilities. Robustness tests and empirical findings closely align with these theories. Additionally, we discover that the likelihood of using the defense mechanism against process fragmentation increases with the firm's expertise in the host nation as well as the alternative worth of the activity's unique knowledge that is outsourced.